PROTECTIVE EFFECT OF HIPPOPHAE SALICIFOLIA ON THE ALUMINIUM INDUCED BEHAVIOURAL AND BIOCHEMICAL CHANGES IN FEMALE WISTAR RATS - C.M.DIVYASHANTHI M.D.; E.MANIVANNAN M.D (International Journal of Pharma and Bio Sciences, 2014)
To analyze the effect of hydroalcoholic fruit pulp extract of Hippophae salicifolia on the influence of aluminium chloride induced changes in serum and tissue antioxidants, tissue ATPases, learning and memory, motor activity and coordination in female Wistar Albino rats.These rats (n=24) were administered H. salicifolia and AlCl3 in the form of solution orally continuously for 60 days. The pharmacological studies included evaluation of antioxidant property, estimation of - lipid peroxidation, reduced glutathione level, catalase, glutathione-S-transferase,superoxide dismutase activities and analysing the effect H. salicifolia on membrane bound adenosine triphosphatases in Alcl3 induced toxicity.The effect of the extract of H. salicifolia on animal behaviour and motor coordination were assessed.Phytochemical analysis of H.salicifolia demonstrated the presence of carbohydrates, glycosides, phytosteroids, fixed oils and fats, saponins, gums and mucilage, tannins and phenolic compounds. Heart and lung of AlCl3 treated group demonstrated a statistically significant increase in lipid peroxidation. AlCl3 and H salicifolia treated group demonstrated increase in the reduced glutathione in lung and catalase activity in heart. An increase in the activity of glutathione-Stransferase was observed in serum, liver, lung and kidney of H. salicifolia treated group. A statistically significant increase in the level of Na+/K+ ATPase was observed in the heart and lung of AlCl3 and H.salicifolia extract treated groups. Also increase in activity of Ca2+ ATPase was observed in kidney of AlCl3, H salicifolia and both AlCl3 and extract treated groups. An increase in the level of Mg2+ ATPase was observed in heart of AlCl3 and H. salicifolia treated group. An increase in the time taken was observed in Jumping box in AlCl3 and H. salicifolia treated groups. In Rota-rod, time taken was increased in H.salicifolia extract treated group. A decrease in the time taken in photoactometer was observed in both AlCl3 and extract treated group. A decrease in the time taken in Hebb-William’s maze was observed in the H.salicifolia treated group. Treatment with AlCl3 demonstrated an increase in tissue catalase in heart and a decrease in glutathione in liver, heart and lung. H.salicifolia suppressed the effect of AlCl3 on liver and heart. H.salicifolia reduced the memory blunting effect of AlCl3.